Effect of Grain Refinement on the Dynamic, Mechanical Properties, and Corrosion Behaviour of Al-Mg Alloy - Haitham M. Ahmed; Hussin A. M. Ahmed; Mohammed Hefni; Essam B. Moustafa (Metals, 2021)
In this investigation, aluminium Al-2.5% Mg cast alloy was modified by adding 0.5 Ti and 0.1 B wt % modifiers to investigate their impact on the dynamic behaviour, as well as the mechanical and microstructure properties. The dynamic properties were analysed experimentally using a free vibration impact test and predicted using finite element methods. This study used a high-resolution polarised optical microscope to analyse the microstructure of the studied alloys and X-ray Powder Diffraction (XRD) analysis to determine the developed phases. Microstructure and mechanical properties were mostly enhanced as a result of grain refining during solidification and through the metal segregation process. The microstructure analysis of the modified alloy showed a significant improvement in the grain refinement; hence, the grains were 10 times finer than the cast alloy. The modified Al-2.5% Mg/Ti-B alloy demonstrated reduced inter-granular corrosion (IGC) than the Al-2.5% Mg standard cast alloy. By incorporating Ti-B modifiers into the composition of the cast Al-Mg alloy, the ultimate tensile strength (UTS), strain (ε), and hardness values (HV) were increased by 30.5%, 100%, and 18.18%, respectively. The dynamic properties of the modified alloy showed an enhancement in the resonant (fn) and damping ratio (ζ) by 7% and 68%, respectively. The predicted resonance frequencies of the investigated alloys showed results close to the experimental dynamic tests.